2011
DOI: 10.1016/j.bbalip.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human atypical kinase ADCK3 rescues coenzyme Q biosynthesis and phosphorylation of Coq polypeptides in yeast coq8 mutants

Abstract: Coenzyme Q (ubiquinone or Q) is a lipid electron and proton carrier in the electron transport chain. In yeast Saccharomyces cerevisiae eleven genes, designated COQ1 through COQ9, YAH1 and ARH1, have been identified as being required for Q biosynthesis. One of these genes, COQ8 (ABC1) encodes an atypical protein kinase, containing six (I, II, III, VIB, VII, and VIII) of the twelve motifs characteristically present in canonical protein kinases. Here we characterize seven distinct Q-less coq8 yeast mutants, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
138
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 84 publications
12
138
0
Order By: Relevance
“…Cytochrome c, which peripherally attaches to the inner mitochondrial membrane through electrostatic interactions with fatty acids and acidic phospholipids [65], was released from the sonicated mitoplasts following salt addition, as expected. These results provide further support for the submitochondrial localization data indicating that yeast Coq7 is a peripheral membrane protein on the matrix side as are Coq1, Coq3, Coq4, Coq5, Coq6, Coq8, and Coq9 polypeptides [20,31,36,49,[66][67][68].…”
Section: Coq2 Is Resistant To Salt Extraction While Other Coq Polypepsupporting
confidence: 72%
“…Cytochrome c, which peripherally attaches to the inner mitochondrial membrane through electrostatic interactions with fatty acids and acidic phospholipids [65], was released from the sonicated mitoplasts following salt addition, as expected. These results provide further support for the submitochondrial localization data indicating that yeast Coq7 is a peripheral membrane protein on the matrix side as are Coq1, Coq3, Coq4, Coq5, Coq6, Coq8, and Coq9 polypeptides [20,31,36,49,[66][67][68].…”
Section: Coq2 Is Resistant To Salt Extraction While Other Coq Polypepsupporting
confidence: 72%
“…Indeed, in yeast, it has been demonstrated that ABC1/Coq8 is required for the phosphorylation of Coq3, Coq5 and Coq7, three enzymes involved in ubiquinone pathway. Moreover, the human Coq8 ortholog ADCK3 rescues the phosphorylation of several Coq proteins in the yeast coq8 mutant as well as the defective phenotype of the strain (Xie et al 2011).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
“…ABC1K protein sequences have sequence motifs typical of a kinase and are thought to function as regulators of ubiquinone synthesis via protein phosphorylation (Poon et al, 2000). Remarkable functional conservation has been demonstrated by complementation of the yeast abc1 mutant with homologs from Arabidopsis (At-ABC1K13) and human (Hs-ABC1K13) (Cardazzo et al, 1998;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although investigation of the PG-localized ABC1K1 using RNA interference (RNAi) suggested an impairment in chlorophyll degradation, the RNAi strategy used the fulllength coding sequence of the gene, thus targeting many of the ABC1K transcripts and confounding the conclusions (Yang et al, 2012). Kinase activity of any of the ABC1Ks remains to be directly demonstrated, though indirect evidence from point mutants in the ABC1K domain of yeast, human, and bacterial ABC1K proteins strongly supports the putative kinase activity (Lagier-Tourenne et al, 2008;Mollet et al, 2008;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%